A note on production yield measure for multiple lines. Issue 4 (1st October 2016) - Pearn, W. L.; Tai, Y. T.; Wu, C. H.
Abstract: In today's globally competitive environment, processes involving multiple manufacturing lines are quite common due to economies of scale considerations. Production yield measure indices Cpk and Cpu are the most popular yield-based indices and have been widely used in manufacturing industries for two-sided and one-sided specification limits, respectively. In this paper, two production yield indices for multiple lines and are considered and the approximate distributions of two natural estimators and are derived. For the convenience of industry applications, the lower confidence bounds and critical values are provided.